Infection risk by oral contamination does not induce immune priming in the mealworm beetle (Tenebrio molitor) but triggers behavioral and physiological responses - Goerlinger, Alexandre; Develay, Charlène; Balourdet, Aude; Rigaud, Thierry; Moret, Yannick (Frontiers in Immunology, 2024)
In invertebrates, immune priming is the ability of individuals to enhance their immune response based on prior immunological experiences. This adaptive-like immunity likely evolved due to the risk of repeated infections by parasites in the host's natural habitat. The expression of immune priming varies across host and pathogen species, as well as infection routes (oral or wounds), reflecting finely tuned evolutionary adjustments. Evidence from the mealworm beetle (Tenebrio molitor) suggests that Gram-positive bacterial pathogens play a significant role in immune priming after systemic infection. Despite the likelihood of oral infections by natural bacterial pathogens in T. molitor, it remains debated whether ingestion of contaminated food leads to systemic infection, and whether oral immune priming is possible is currently unknown. We first attempted to induce immune priming in both T. molitor larvae and adults by exposing them to food contaminated with living or dead Gram-positive and Gram-negative bacterial pathogens. We found that oral ingestion of living bacteria did not kill them, but septic wounds caused rapid mortality. Intriguingly, the consumption of either dead or living bacteria did not protect against reinfection, contrasting with injury-induced priming. We further examined the effects of infecting food with various living bacterial pathogens on variables such as food consumption, mass gain, and feces production in larvae. We found that larvae exposed to Gram-positive bacteria in their food ingested less food, gained less mass and/or produced more feces than larvae exposed to contaminated food with Gram-negative bacteria or control food. This suggests that oral contamination with Gram-positive bacteria induced both behavioral responses and peristalsis defense mechanisms, even though no immune priming was observed here. Considering that the oral route of infection neither caused the death of the insects nor induced priming, we propose that immune priming in T. molitor may have primarily evolved as a response to the infection risk associated with wounds rather than oral ingestion.